Coexistence of nasal reactivity to allergens with and without IgE sensitization in patients with allergic rhinitis. Issue 7 (12th February 2020) - Eguiluz‐Gracia, Ibon; Fernandez‐Santamaria, Ruben; Testera‐Montes, Almudena; Ariza, Adriana; Campo, Paloma; Prieto, Ana; Perez‐Sanchez, Natalia; Salas, Maria; Mayorga, Cristobalina; Torres, Maria Jose; Rondon, Carmen
Abstract: Background: Allergic rhinitis (AR) and local allergic rhinitis (LAR) are defined by nasal reactivity to aeroallergens with and without positive skin prick test (SPT), respectively. In this study, we aimed to investigate whether both types of allergen‐specific reactivity can coexist in the same individual. Methods: Forty‐eight patients with perennial rhinitis symptoms and positive SPT with seasonal allergens only (discrepant group) were subjected to consecutive nasal allergen challenges (NAC) with seasonal (NAC‐S) and perennial allergens (NAC‐P). A nasal lavage was collected before and after the NACs to measure eosinophil cationic protein (ECP). A basophil activation test (BAT) with seasonal and/or perennial allergens was performed in ten patients from the discrepant group and in six seasonal allergic rhinitis (SAR), eight perennial local allergic rhinitis (LAR), six nonallergic rhinitis (NAR), and six healthy control (HC) individuals. Results: All patients in the discrepant group tested positive in the NAC‐S, and 41 of them (85.4%), also in the NAC‐P (group A). Conversely, seven patients tested negative in the NAC‐P (group B). ECP in the nasal lavage increased after the NAC‐P in the group A ( P = .004), but not in the group B. The BAT with seasonal allergens was positive in 100% of SAR and group A cases, whereas the BAT with perennial allergens was positive in 37.5% and 60% of LAR and group A cases, respectively. All NAR and HC subjects tested negative for the BAT. Conclusion: This study shows that nasal reactivity to aeroallergens with and without positive SPT can coexist in the same patient. We propose the term dual allergic rhinitis for this rhinitis phenotype. Abstract : We demonstrate that a significant proportion of rhinitis patients with SPT positivity to seasonal allergens only, but suffering from perennial symptoms display nasal reactivity to both perennial and seasonal allergens. Nasal reactivity to allergens is associated with the increase of ECP in the nasal secretions, regardless of the atopic status for the corresponding allergen. Nasal reactivity to allergens can be associated with positive basophil activation test responses, regardless of the atopic status for the corresponding allergen.